Regularities and irregularities in rhetorical move structure of linguistics abstracts in research articles - Delaram Khansari,; Chan, Swee Heng; Chan, Mei Yuit; Tan, Helen (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
Awareness of abstract writing skill plays an important role for research article (RA) abstract writers to meet the discourse community expectations. In academic writing, writers should persuade readers to read the whole article by writing an effective abstract in terms of both content and rhetorical structure. This paper utilised Swales’ (1990) theory as considers abstract as an independent discourse because of its distinctive function and indicates the content and structure of the whole text. Swales also highlights the format of the abstract as having I-M-R-D pattern. The underlying assumption is that the associated RAs follow the IMRD structures and their abstracts are also likely to exhibit the same move pattern. This study investigated 130 English research article abstracts in linguistics journals in order to identify the move patterns found in RA abstracts in terms of moves and steps. In addition, it established move cycling in the structuring of an abstract. The findings indicated that 63.84% of the abstracts followed the IMRD structure that was premised to reflect the structure of the main text. Findings from this research provide new insights into abstract writing in linguistics articles, in particular, with regard to the actual practice in the use of the IMRD move patterns and how the related genres in RA are similar or different. These findings have pedagogical implications as writers could be given training in the various aspects of writing to satisfy the rhetorical structure for information flow.